(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)

来源:学生作业帮助网 编辑:作业帮作业网 时间:2021/09/24 04:19:46
(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)(2又7/9除以1/6+1/3)×(32/5-1又2/5×1

(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)
(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)

(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)
(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)
=(25/9X6+1/3)X(32/5-7/5X12/17)
=(50/3+1/3)X(32/5-84/85)
=(51/3)X(92/17)
=92

(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)
=92

(2又7/9除以1/6+1/3)×(32/5-1又2/5×12/17)
=(50/3+1/3)×(32/5-7/5×12/17)
=(50/3+1/3)X(32/5-84/85)
=(51/3)X(92/17)
=92

=(25/6*6+1/3)*(32/5-7/5*12/17)
=(50/3+1/3)*(32/5-84/85)
=17* (544/85-84/85)
=17* 92/17
=289/17 * 92/17
=197/17